2020
DOI: 10.1021/acsomega.0c03759
|View full text |Cite
|
Sign up to set email alerts
|

IC50 Evaluation of Platinum Nanocatalysts for Cancer Treatment in Fibroblast, HeLa, and DU-145 Cell Lines

Abstract: Cancer is a major public health problem being one of the main causes of morbidity and mortality today. Recent advances in catalytic nanomedicine have offered new cancer therapies based on the administration of nanoparticles (NPs) of platinum (Pt) dispersed in catalytic mesoporous nanomaterials (titania, TiO 2 ) with highly selective cytotoxic properties and no adverse effects. A half maximal inhibitory concentration (IC 50 ) study was carried out in cancerous cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The values of relative cell viability as a function of PS concentration allowed for the calculation of the half-maximal inhibitory concentration (IC 50 ) for the different chemicals tested. IC 50 is usually employed to evaluate a substance efficacy and the concentration able to inhibit cell growth [ 36 ]. The IC 50 values are displayed in Table 1 ; however, for some compounds, only a lower limit could be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The values of relative cell viability as a function of PS concentration allowed for the calculation of the half-maximal inhibitory concentration (IC 50 ) for the different chemicals tested. IC 50 is usually employed to evaluate a substance efficacy and the concentration able to inhibit cell growth [ 36 ]. The IC 50 values are displayed in Table 1 ; however, for some compounds, only a lower limit could be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that docetaxel and gemcitabine exhibited higher IC50 values in the low‐risk groups. IC50 is the drug concentration that induces apoptosis in 50% of tumor cells, which can reflect the degree of drug resistance of tumor cells 36–38 . This result suggests that chemotherapeutic drug therapy may be more suitable for patients with high‐risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…They claim that the cytotoxicity caused by the Pt NPs could be due to the release of Pt ions. [ 101 ] There is a report on a comparative study in which the cytotoxic effects of major three noble metal nanoparticles (Au NPs, Ag NPs, and Pt NPs) using zebrafish models were studied. It was confirmed that Pt NPs cause these models to hatch more slowly, have lower heart rates, and have less responsive skin to touch.…”
Section: Toxicity Concernsmentioning
confidence: 99%